International students’ experiences with changing policy: A qualitative study from middle Tennessee - Marbang, Phattra; McKinzie, Ashleigh E.; Eller, Jackie; Leggett, Ida F (Journal of Interdisciplinary Studies in Education, 2021)
This qualitative study utilizes seventeen international students’ experiences in the U.S. Specifically, we examine the aspects of immigration regulations and policies regarding international students and the students’ reactions to those policies—from becoming a legal alien, to maintaining lawful status, to job planning after graduation. This research suggests the current United States administration has created a moral panic over immigration, or the threat of immigration. As a result, these political rhetoric impact a negative feeling to F-1 international students as well as decision making after graduation.